Tropopause dynamics and temperature anomalies on the Black Sea surface - Manev, Angel (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The suggested research analyzes the tropopause dynamics during the short-term temperature anomalies on the Black Sea surface for a period of 11 years. Satellite data for the condition of the tropopause and the temperature fields on the sea surface are used as a basis from several satellite systems. Tropopause uplifting is registered almost always before the onset of anomalous surface heating process. Issues are dis-cussed for the generation of the temperature anomalies and their connection with the atmospheric processes.